Difficulties in Tax Allocation on General Price-Level Increases. - Richard, Donald L. (The Accounting Review, 1968)
Abstract The general theory of tax allocation is deemed to be appropriate within a period to the income components as well as between periods in order to obtain fairness in financial statement presentation. The matching of income components and their applicable taxes is a basic process of income determination and should be important in current-cost statements as well as in historical-cost statements. Current-cost presentations have been brought into increasing prominence by the American Accounting Association's "A Statement of Basic Accounting Theory." One of the foremost recommendations of the statement was to present current-costs as supplementary information in an attempt to overcome the criticism of historical-cost information. In addition to studying the tax allocation within a period used on general price-level increases in "A Statement of Basic Accounting Theory," this paper will recommend an alternative approach as the best of several other possibilities to be considered, using figures from the American Accounting Association's illustrated statements.